ECOLOGICAL-ECONOMIC ZONING OF THE CITY OF ALTINOPOLIS - SP, BRAZIL - Crivelenti, Rafael C. [UNESP]; Bueno, Celia R. P. [UNESP]; Pires, Jose S. R.; Francisco, Jose; Lessi, Bruno F. (Soc Brasil Engenharia Agricola, 2016)
Since colonial times, Brazilian land use has been made under an extractivist model at the expense of deforestation, increasing soil and vegetation depletion, stream siltation, as well as loss of biodiversity. An ecological-economic zoning (EEZ) has been taken as feasible alternative to guide public policies aimed at city land-use planning. This study focused on designing an EZZ for the city of Altinopolis, in Sao Paulo state (Brazil), by means of geographical information systems (GIS). Information and maps delineated six land-use areas, in which 30% covered areas under environmental protection, 45% over areas with groundwater recharge potential, which should be intended to restoration. Furthermore, around 70% of the territory show potential to be grown with agroforestry systems due to soil, climate and relief conditions. These results point out demand for further public policies to encouraging preservation of existing forests and restoration of degraded areas, mainly those covering groundwater-recharge areas.
Keywords: geographical information systems; soil and water preservation; environmental planning; land use